262 Effect of Isoleucine and Added Valine on Performance, and gut Microbiota Composition of Pigs fed with Very low Protein Diets. (21st September 2022) - Goodarzi, Parniyan; Wileman, Caitlyn M M; Habibi, Mohammad; Walsh, Katherine; Sutton, Julia; Shili, Cedrick n; Chai, Jianmin; Zhao, Jiangchao; Pezeshki, Adel
Abstract: Very low protein (VLP) diets decrease the nitrogen excretion from pigs, but these diets depress the performance even when the first four limiting amino acids (FFL; i.e. Lys, Met, Thr and Trp) are added. Supplementation of Val above and Ile at NRC (2012) levels has shown promising effects on performance of pigs fed with VLP diets. The objective of this study was to investigate the effect of a mixture of Val above and Ile at NRC levels on growth and gut microbiota in pigs fed with VLP diets. Three-week-old, weaned piglets (n = 40) were assigned to: 1) positive control (PC): normal protein diet; 2) negative control (NC): VLP diet with FFL at NRC levels; 3) VA: NC with Val above NRC; 4) IL: NC with Ile at NRC level; 5) VAIL: NC with Val above and Ile at NRC levels. Following 5 weeks of data collection, colon contents were collected. The data were analyzed by GLM procedure followed a t-test with Benjamini-Hochberg correction (SPSS). Pigs fed with NC had decreased average daily gain (ADG) and average daily feed intake (ADFI), compared with PC (P< 0.05). VAIL had less ADG than PC, but that tended to have greater ADG than NC (P< 0.1). Further, VAIL had a similar ADFI as PC (P>0.05) and tended to have greater ADFI than NC (P< 0.1). Compared with PC and NC, pigs fed with VAIL had a higher thermal radiation (P< 0.05). Relative to PC, the colon content of NC was enriched in Pasteurellaceae while those fed with VAIL had a greater abundance of Bacillus, Brevibacillus, Enterococcus, Actinobacteria, which might contribute to improved performance of pigs fed with VAIL diets. Overall, supplementation of a mixture of Val greater than NRC and Ile at NRC into the VLP diets partially improved the performance, which is likely linked with alterations in gut microbiota composition.